2016
DOI: 10.1039/c5cc09650b
|View full text |Cite
|
Sign up to set email alerts
|

Selective reduction of carbon dioxide to bis(silyl)acetal catalyzed by a PBP-supported nickel complex

Abstract: The selective reduction of CO2 to the formaldehyde level remains an important challenge and to date only a few catalysts have been developed for this reaction. Herein, we report an efficient catalyst that consists of a bis(phosphino)boryl nickel hydride complex in combination with B(C6F5)3, for the highly selective hydrosilation of CO2 to bis(silyl)acetal derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 37 publications
(3 reference statements)
7
50
0
1
Order By: Relevance
“…[1][2][3] A variety of catalysts have been discovered and developed for this reaction, including complexes of Co, 4 Cu, [5][6][7][8] Ir, [9][10][11][12][13][14] Ni, [15][16][17] Pd/Pt, 18 Rh, 19 Ru, [20][21][22][23][24][25] Sc, 26 Zn, [27][28][29] and Zr, 30 frustrated Lewis pairs, [31][32][33][34][35][36] organocatalysts, [37][38][39][40][41][42] alkali metal carbonates, 43 and even polar solvents such as DMF. 38 These reactions result in various reduction products including silyl-formates, -acetals, andethers, CO, and methane.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A variety of catalysts have been discovered and developed for this reaction, including complexes of Co, 4 Cu, [5][6][7][8] Ir, [9][10][11][12][13][14] Ni, [15][16][17] Pd/Pt, 18 Rh, 19 Ru, [20][21][22][23][24][25] Sc, 26 Zn, [27][28][29] and Zr, 30 frustrated Lewis pairs, [31][32][33][34][35][36] organocatalysts, [37][38][39][40][41][42] alkali metal carbonates, 43 and even polar solvents such as DMF. 38 These reactions result in various reduction products including silyl-formates, -acetals, andethers, CO, and methane.…”
Section: Introductionmentioning
confidence: 99%
“…Under similar conditions, Serrano and Rodriguez evaluated a Nickel PBP-complex for the formation of bis(silyl) methylene acetal from CO2 in presence of Et3SiH with high selectivities (78->99%) and moderate to high conversion (41-91%) at 70°C. 17 Already in 2013, Berke and coworkers reported the hydrosilylation of CO2 using a Frustrated Lewis Pair (FLP) consisting for example of a rhenium hydride and B(C6F5)3 (Scheme 12) at 80°C. 21 Here the authors reported yields of ~90%.…”
Section: Scheme 12 Metal Catalysed Reduction Of Co2 With Et3sih Yielmentioning
confidence: 99%
“…TES-promoted reactions that involve metal catalysts (Pd, Mo, Ni, Au, Mn or Ru complexes) have been successfully used for the regioselective hydrogenation of olefins, [22][23][24] imines, [25] nitriles, [26] nitro derivatives [27] and carbonyl compounds. [28][29][30][31] Alternatively, TES mixed with a suitable Brønsted acid can be used under metal-catalyst-free conditions, [32][33][34][35] e.g., for the reductive cleavage of sulfides, [36] ethers, [37,38] hydroxides [39,40] and acetoxy groups. [41] A TES/trifluoroacetic acid (TFA) mixture can also be used as the reducing agent to yield unsaturated heterocycles.…”
Section: Introductionmentioning
confidence: 99%